1999
DOI: 10.1161/01.atv.19.2.281
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Shear Stress Induction of the Tissue Factor Promoter In Vitro and In Vivo Is Mediated by Egr-1

Abstract: Abstract-Hemodynamic forces such as fluid shear stress have been shown to modulate the activity of an expanding family of genes involved in vessel wall homeostasis and the pathogenesis of vascular disease. We have investigated the effect of shear stress on tissue factor (TF) gene expression in human endothelial cells (ECs) and in a rat arterial model of occlusion. As measured by reverse transcriptase polymerase chain reaction, exposure of ECs to 1.5 N/m 2 shear stress resulted in a time-dependent induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 43 publications
3
80
0
2
Order By: Relevance
“…Lin et al 21 and Houston et al 22 both reported that shear stress alone (no cytokine exposure) transiently induced TF mRNA over periods of 1 to 3 hours. Transcription factors likely involved in these shear stress-induced changes in TF mRNA include Sp1, whose increased activity is associated with hyperphosphorylation, 21 and/or Egr-1, 22-24 but not nuclear factor-B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al 21 and Houston et al 22 both reported that shear stress alone (no cytokine exposure) transiently induced TF mRNA over periods of 1 to 3 hours. Transcription factors likely involved in these shear stress-induced changes in TF mRNA include Sp1, whose increased activity is associated with hyperphosphorylation, 21 and/or Egr-1, 22-24 but not nuclear factor-B.…”
Section: Discussionmentioning
confidence: 99%
“…4 In those studies, either human umbilical vein ECs were subjected to 12 dyne/cm 2 for 1 to 2 hours 21 or human aortic ECs were exposed to 15 dyne/cm 2 for 1 to 3 hours. 22 Lin et al found that TF mRNA by Northern blotting was essentially no longer present after 6 hours; Houston et al, who performed RT-PCR, did not look beyond 3 hours. Although the present work does not address this issue, we did find that TF antigen at 3 hours increased with increasing shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…89,90 Hypertension increases shear stress leading to activation of NFκB and Egr-1, and subsequently to upregulation of TF gene expression. 91,92 Angiotensin-convertingenzyem (ACE) inhibitors downregulate TF expression in vivo, 93 while angiotensin II upregulates it in vascular cells via the angiotensin II type 1 receptor. 94 …”
Section: Hypertensionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Egr-1, which encodes a serum-inducible zinc finger nuclear phosphoprotein, is rapidly induced in cultured cells by a wide variety of mitogenic and nonmitogenic stimuli. In endothelial cells, Egr-1 has been shown to be activated by acidic fibroblast growth factor, 24 basic fibroblast growth factor, 25,26 vascular endothelial growth factor (VEGF), 27 epidermal growth factor (EGF), 28,29 shear stress, [30][31][32] cyclical strain, 33 and hypoxia. 34,35 In turn, the Egr-1 transcription factor may induce the expression of a wide range of target genes including PDGF-A, 36 PDGF-B, tissue factor (TF), 27 Flt-1, 37 transforming growth factor (TGF)-␤, tumor necrosis factor (TNF)-␣, urokinasetype plasminogen activator (u-PA), and metalloproteinases.…”
Section: Introductionmentioning
confidence: 99%